ڕاڤەی تیۆرە کۆمەڵایەتییەکان بۆ تاوانە خێزانییەکان به‌كاریگه‌ری فاكته‌ره‌كانی دامه‌زراوه‌ كۆمه‌ڵایه‌تییه‌كان و په‌ڕگیری هزریی - عبدالله‌, پ.د.ئاسۆ ابراهیم; محمد, م.هیوا یاسین (Sulaimani Journal for Humanities, 2023)
This research (explaining social theories for family crimes, through the factories of social institutions and intellectual extremism), is an attempt to explain the phenomenon of family crimes from the of sociological perspective because family crimes are one of the social phenomena that have faced the majority of societies and have directly impacted on individuals, families, and societies in the past and now. Meanwhile, this crime is the main factor for family separation, and it creates a threat to the security of societies. Therefore, it is important to research this subject. This research aims to explain the anomie theory, especially Émile Durkheim and Robert Merton perspectives, explain Edwin Sutherland's perspective on the differential association theory, and discover the explanation of the theory of differential opportunities focused on Richard Cloward and Lioyd Ohlin’ views. Finally, connecting the explanation of used theories with the content of the research that is explaining the social theories for family crimes using institutional and intellectual extremism. In this research, the method of analytical description has been used. The parts of the research are the elements of the research, displaying the anomie, differential association, and differential opportunities theories. The research has reached some important conclusions. Based on Durkheim’s opinion, inequality in the division of labor in society and both anomic and altruistic suicides are the factors of family crimes. Furthermore, in Morten’s view, inequality and injustice among family members in accessing legitimate tools, and the pattern of innovators and rebellions are related to conducting criminal behavior, including family crimes. In addition, Sutherland believes that human beings learn criminal behavior because of the surrounding social environment. The human being is not born guilty, but he/she learns criminal behavior and family crimes through interaction, conversation, imitation, media, and contact with others in different groups. According to Cloward and Ohlin, criminal groups are in the lower classes of society with great ability and experience, but they cannot achieve their goals because they do not have legitimate opportunities. Young people are also committing crimes using illegitimate means because they are annoyed with the religious, educational, family, and media systems. Each of the institutions is a factor in carrying out intellectual extremism and family crimes.
Keywords: تاوان تاوانە خێزانییەكان خێزان پەڕگیری هزریی ئەنۆمی فێربوون جیاوازی دهرفەتەكان